Determinants Of Economic Growth In Organizations Of Islamic Cooperation (OIC) Member Countries With Governance Index As Moderating - Nur Umaima Wafia Marwiah; Muhammad Ghafur Wibowo (Relevance: Journal of Management and Business, 2023)
Economic growth is one of the important indicators that can be used for economic development in a country. However, the high incomes that are not matched by sustainable development can lead to economic growth gaps. This study is intended to determine the effect of international trade, inflation, and interest rates by including the governance index variable as a moderating variable on economic growth. The object of research used is all countries of the Organization of Islamic Cooperation (OIC) by 57 countries, but limited data, so there are 27 countries selected for the period 2010-2019. This study uses the approach GMM (Generalized Method of Moments) to analyze data. Then for the use of the approach to analyze state governance variables using the Moderated Regression Analysis (MRA). The results of statistical tests show that international trade variables have a significant positive effect on economic growth except for inflation and interest rates which have a significant negative effect. This causes the negative effect of these variables due to the lack of control carried out by government policies. However, the governance index can moderate international trade, inflation, and interest rates in their impact on economic growth. This study confirms that good governance can improve the economy in OIC member countries. Keywords: Economic Growth; International Trade; Inflation; Interest Rates, Governance Index